Estilos de vida nas telenovelas: cultura do consumo, identidade e pós- modernidade - Gomes, Vanda Viana (2012)
What is the possible contribution of Brazilian soap operas in the diffusion of consumer culture and how this relationship influences the fragmentation of identity in postmodernity? In this context, the role of lifestyles? The purpose of this paper is to discuss these issues by examining what is postmodernism and how consumer culture contributes to the fragmentation of identity, with the spread of lifestyles. The process is analyzed with emphasis on mediatization and then to soap operas.